Skills that are valued in the knowledge economy: an examination of the experience of French workers in the 2000s. (1st October 2012) - Fabienne Berton
Abstract : An examination of the professional careers of French workers during the 2000s, shows that some workers gave themselves wholeheartedly to the knowledge economy, some attempted to withdraw from it and others were clearly excluded from it. The first group demonstrated an ability to handle complex employment relationships, to show substantial flexibility in their hours and place of work, and to maintain a professional network and up-to-the-minute personal communications technology, whereas the other two groups either did not possess these aptitudes or did not wish to acquire them. Those who decided to opt out of the knowledge economy mainly did so because they were disinclined or because they were reluctant to adapt to the requirements of a large organisation undergoing restructuring. A move towards the care sector via professional reconversion highlighted their awareness of interpersonal relations and human wellbeing. Those who found themselves frozen out of the knowledge economy were recognisable by their isolation, their inability to retain professional networks and the difficulties they encountered in envisaging the next step in their careers.